Perancangan Aplikasi Administrasi Pada Fakultas Keguruan dan Ilmu Pendidikan Menggunakan Java Netbeans Ide 8.1 dan Mysql - Widyastuti, Rini; Amelia, Riska; Gea, Yufen Yuliandri; Murlena, Murlena; Syahindra, Wandi (Arcitech: Journal of Computer Science and Artificial Intelligence, 2022)
Faculty of Teacher Training and Administrative Education is an administrative service at Bung Hatta University, Padang City. The data collection process for incoming and outgoing letters at the FKIP Administrative Unit is still said to be using the manual method. This study aims to produce a desktop-based administrative information system at the Teaching and Education Faculty with the aim of facilitating managers in recording incoming and outgoing mail numbers. This study uses the waterfall method with the design stages starting from analysis, system design using models including Context Diagrams, Data Flow Diagrams (DFD), and Unified Modeling Language (UML). Database storage using MySQL. The design phase ends with testing the program to produce an administration application at the Bung Hatta University FKIP using Java Netbeans IDE 8.1 and MySQL. This application can facilitate and speed up the process of data collection and search for incoming and outgoing mail numbers in the FKIP Administration.